Development of Teacher Position in Islamic Education Institutions: Teachers as Professional Educators - Imam Muhayat (ISTAWA, 2019)
Coaching is an effort, action, and activities that are carried out efficiently and effectively to obtain better results. While growth is a thing (state) grows; progress (progress etc.). So that guidance on the growth of positions of teachers can be defined as efforts, actions, and activities carried out efficiently and effectively to obtain better results. In this case, a professional job, it would be wise to discuss one-word teacher, position, and licensed as a keyword that can be used as a professional position.Thus this text will discuss in detail the formation of teacher positions in Islamic educational institutions.Pembinaan merupakan usaha, tindakan, dan kegiatan yang dilakukan secara efisien dan efektif untuk memperoleh hasil yg lebih baik. Sedangkan pertumbuhan adalah hal (keadaan) tumbuh; perkembangan (kemajuan dsb). Sehingga pembinaan terhadap pertumbuhan jabatan guru dapat didefinisikan sebagai usaha, tindakan, dan kegiatan yang dilakukan secara efisien dan efektif untuk memperoleh hasil yg lebih baik dalam pertumbuhan atau perkembangan jabatan guru. Dalam hal ini guru sebagai jabatan professional, alangkah bijaknya jika dibahas satu-persatu pengertian dari kata guru, jabatan, dan profesional sebagai kata kunci yang dapat memberikan gambaran tentang apa yang dimaksud dengan guru sebagai jabatan profesional tersebut.Dengan demikian naskah ini akan membahas secara detail perihal pembinaan jabatan guru di lembaga pendidikan Islam.